Hand hygienic disinfection of nurses - knowledge and its practical use - Václavíková, Klára; Marková, Iva; Kopecký, Michal; Ochtinská, Hana; Jeřábková, Veronika (Nursing in the 21st Century, 2021)
HAND HYGIENIC DISINFECTION OF NURSES - KNOWLEDGE AND ITS PRACTICAL USEAim. To find out the level of theoretical knowledge of nurses working in the internal medicine and surgical wards about hygienic hand disinfection and to evaluate its application during work performance.Material and methods. A questionnaire was conducted, supplemented by observations with records in the observation sheets. The group of respondents consisted of 60 nurses working in the internal medicine and surgical wards.Results. The theoretical knowledge of a selected sample of nurses reaches an average level. The observations have proved that nurses do not put emphasis on hygienic hand disinfection during everyday activities and the level of quality of hygienic hand disinfection is low.Conclusions. Hygienic hand disinfection is one of the important indicators of the quality of the health care provided. It is necessary to increase the level of the theoretical knowledge of healthcare professionals and, at the same time, to enable healthcare professionals to practise hygienic hand disinfection and to provide efficient feedback.